Gender impact on safety and efficacy in lenvatinib treated patients with radioiodine-refractory differentiated thyroid cancer (GISEL study) - Giulia Puliani; Marta Bianchini; Carlotta Giani; Laura Valerio; Alice Nervo; Giulia Sapuppo; Giorgio Grani; Cristina Dalmiglio; Simone De Leo; Rosa Lauretta; Marilda Mormando; Irene Terrenato; et al. (European Thyroid Journal)
Introduction: Little is known about sex differences in lenvatinib treatment safety and efficacy. Methods: Real-word retrospective Italian multicenter study enrolling patients with radioiodine-refractory differentiated thyroid cancer treated with lenvatinib. Results: A total of 138 patients (64 females) were included, with a median follow-up of 26 months (2–72). More men performed physical activities (34% vs 17%, P = 0.024). The frequency of smoking and alcohol consumption was higher in men (58% vs 33%, P = 0.003; 45% vs 17%, P = 0.001). We did not find sex differences in lenvatinib dose reduction due to adverse events (AEs) (78% females vs 85% males). Ninety-nine percent of patients developed at least one adverse event (AE), with no sex difference in their number and the time to first AE. Severe AEs occurred in 74% of males and 66% of females (P = 0.398), with a mean dose of 18.2 mg (±5.7), and a median time to the first serious AE of 9 weeks (1–154). Stomatitis/mucositis and hematological disorders were more frequent in females (48% vs 30%, P = 0.016; 17% vs 4%, P = 0.011). Gastrointestinal disorders were higher in males (15% vs 2%, P = 0.010). Eighty-seven patients interrupted lenvatinib due to AEs (median time: 3 months (0–48), mean dose: 17 mg ±5.5). Discontinuation occurred in 21 patients, five for severe AEs. No sex differences were found in progression-free survival, overall survival or disease control rate. Liver metastases were associated with disease progression (HR: 3.73, 95% CI: 1.06–13.12, P = 0.040) or death (HR: 4.82, 95% CI: 1.75–13.25, P = 0.002) only in females. Conclusion: Lenvatinib is effective in both sexes and exhibits a good safety profile, with a sex difference in the frequencies of some adverse events.